2016
DOI: 10.1038/srep20643
|View full text |Cite
|
Sign up to set email alerts
|

Basic FGF or VEGF gene therapy corrects insufficiency in the intrinsic healing capacity of tendons

Abstract: Tendon injury during limb motion is common. Damaged tendons heal poorly and frequently undergo unpredictable ruptures or impaired motion due to insufficient innate healing capacity. By basic fibroblast growth factor (bFGF) or vascular endothelial growth factor (VEGF) gene therapy via adeno-associated viral type-2 (AAV2) vector to produce supernormal amount of bFGF or VEGF intrinsically in the tendon, we effectively corrected the insufficiency of the tendon healing capacity. This therapeutic approach (1) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 62 publications
(95 reference statements)
3
58
0
3
Order By: Relevance
“…Exogenous delivery of bFGF in a rabbit model of Achilles tendon repair resulted in enhanced cell maturation and improvements to the structural organization of the tendon . Others have seen increased collagen deposition as a result of bFGF treatment via gene therapy and increased deposition of elastin as a result of IGF‐I in other tissue types . In the current study, treatment of tenocytes with 50% ASA CM significantly increased collagen and elastin deposition at both 7 and 14 days.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Exogenous delivery of bFGF in a rabbit model of Achilles tendon repair resulted in enhanced cell maturation and improvements to the structural organization of the tendon . Others have seen increased collagen deposition as a result of bFGF treatment via gene therapy and increased deposition of elastin as a result of IGF‐I in other tissue types . In the current study, treatment of tenocytes with 50% ASA CM significantly increased collagen and elastin deposition at both 7 and 14 days.…”
Section: Discussionsupporting
confidence: 56%
“…Placental‐derived tissues such as ASA are known to contain growth factors, including aFGF, bFGF, PDGF‐BB, IGF‐I, TGF‐β1, and TGF‐β3 . Interestingly, others have shown that exogenous growth factors, including aFGF, bFGF, TGF‐β3, VEGF, human recombinant epidermal growth factor (hrEGF), and PRP, have enhanced tenocyte migration and/or proliferation in preclinical models of tendon injury. Furthermore, evidence suggests that a combination of factors, including bFGF, PDGF‐BB, and IGF‐I, were superior to each factor individually in promoting tenocyte proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…The FGF2 gene was chosen for a number of reasons. Firstly, FGF is one of main growth factors for tissue repair, and its major action is in the promotion of collagen production, tendon development, proliferation of tenocytes and it also plays a role in promoting the expression of a series of other growth factor genes ( Tang et al, 2016 ). Additionally, FGF is down-regulated during tendon repair under normal circumstances and low levels of FGF may be a principle reason for poor healing potential of the tendon ( Tang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the adhesion extent significantly decreased 6 and 8 weeks post-injury; however, tendon strength unfortunately was also reduced [119]. Another study showed that gene therapy to produce supernormal amounts of bFGF or VEGF supported the intrinsic tendon healing in a chicken flexor tendon model-with a significantly higher tendon strength by 68-91% from week 2 after AAV2-bFGF treatment and by 82-210% from week 3 after AAV2-VEGF compared to controls [120]. At the same time, adhesion formation was not adversely affected.…”
Section: Cellular Approachesmentioning
confidence: 99%